Bodily pleasure matters: velocity of touch modulates body ownership during the rubber hand illusion - Crucianelli, Laura; Metcalf, Nicola K.; Fotopoulou, Aikaterini (Katerina); Jenkinson, Paul M. (Frontiers in Psychology, 2013)
The sense of body ownership represents a fundamental aspect of our self-consciousness. Influential experimental paradigms, such as the rubber hand illusion (RHI), in which a seen rubber hand is experienced as part of one’s body when one’s own unseen hand receives congruent tactile stimulation, have extensively examined the role of exteroceptive, multisensory integration on body ownership. However, remarkably, despite the more general current interest in the nature and role of interoception in emotion and consciousness, no study has investigated how the illusion may be affected by interoceptive bodily signals, such as affective touch. Here, we recruited 52 healthy, adult participants and we investigated for the first time, whether applying slow velocity, light tactile stimuli, known to elicit interoceptive feelings of pleasantness, would influence the illusion more than faster, emotionally-neutral, tactile stimuli. We also examined whether seeing another person’s hand versus a rubber hand would reduce the illusion in slow versus fast stroking conditions, as interoceptive signals are used to represent one’s own body from within and it is unclear how they would be integrated with visual signals from another person’s hand. We found that slow velocity touch was perceived as more pleasant and it produced higher levels of subjective embodiment during the RHI compared with fast touch. Moreover, this effect applied irrespective of whether the seen hand was a rubber or a confederate’s hand. These findings provide support for the idea that affective touch, and more generally interoception, may have a unique contribution to the sense of body ownership, and by implication to our embodied psychological “self”.